Head Over Heels - Romantic Relationship Ensuing Conflict among Peer Interactions of Dycian Freshmen Class (American Journal of Human Psychology, 2023)
It is the very nature of human individuals to feel love and be loved, the need for intimacy and romantic love from their fellow and love from their friends. From there, people slowly learned and grew as individuals. Hence, all people yearn to be held by someone, to have a partner with whom they may spend the rest of their lives. The objective of this study is to explore and understand the conflicts that may ensue in entering romantic relationships towards their peer interactions. Anchored in this study are Duck’s Model of Relationship Breakdown, Aristotle’s Theory of Friendship, and the Social Penetration Theory. Specifically, it sought to answer the following questions: 1. What are the perspectives of the informants about: A. romantic relationship, B. friendship. 2. What are the conflicts that may arise in entering a romantic relationship to their peer relationship? 3. What are the remedies to the conflicts that may ensue while engaging in a romantic relationship in regards to their peer interaction? Semi-structured interviews and non-probability sampling were used in the study, which was qualitative phenomenological research. Significant statements were chosen from the verbatim transcripts of the interviews. Then, in order to identify the emerging themes, these were divided into theme clusters. The following themes emerged from the interviews: Matter of Choice, Inevitable Connection, Conventional Stressors, and Relationship Key Factors. The researchers’ findings were as follows: 1. A. Romantic relationship can be seen as a choice to make, B. Friendship is built through inescapable connections made from the very start; 2. Conflicts arising are the common stressors in a relationship; and 3. There are key factors to mitigate these ensuing conflicts as entering romantic relationships impacts peer interactions.